Profiling and predicting performance of indoor rock climbers - Hamid Arazi; Amir Rashidlamir; Mohammad Zahed Abolhasani; Somayeh Askari Hosaini (Universidade Federal de Santa Catarina, 2018)
The aim of this study is to establish somatotype and profile the anthropometric and biomotor characteristics of indoor rock climbers. Fourteen elite level male and ten recreational female Iranian indoor rock climbers completed a battery of tests. All anthropometric measurements were performed according to the recommendations of international standards for anthropometric assessment. Upper body strength and endurance were assessed by isometric tests. Explosive power and balance were also evaluated by Sargent jump and Star Excursion Balance Test (SEBT), respectively. Samples' somatotypes were calculated by the method of Heath and Carter. Pearson's correlation coefficient and partial correlations were calculated and stepwise multiple regression analyses were implemented to determine a set of best predictors of elite male climbers' ability. Shoulder width, body fat content, upper-body strength and endurance for females, showed the most correlation with the climbing ability (range: r = 0.46-0.7, p ≤ 0.05), while among the male samples, these correlations with the climbing ability were mostly between WHR, absolute and relative to body mass handgrip strength, SEBT performance and the left-hand digit ratio. The results of stepwise multiple regression revealed that the SEBT performance in the posterior direction of right foot stance and Upper Extremity Girth Index are able to explain 62% of the variance of climbing ability. It is likely that decreasing the fat mass has no direct impact on the climbers' performance. Also, SEBT performance is able to predict 35% of climbing performance. Hence, it seems balance exercises could be effective in improvement of climbing performance.